Using multiple high-count electrode arrays in human median and ulnar nerves to restore sensorimotor function after previous transradial amputation of the hand - Clark, Gregory A.; Wendelken, Suzanne; Page, David M.; Davis, Tyler; Wark, Heather A. C.; Normann, Richard A.; Warren, David J.; Hutchinson, Douglas T. (2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2014)
Peripheral nerve interfaces that can record from and stimulate large numbers of different nerve fibers selectively and independently may help restore intuitive and effective motor and sensory function after hand amputation. To this end, and extending previous work in two subjects, two 100-electrode Utah Slanted Electrode Arrays (USEAs) were implanted for four weeks in the residual ulnar and median nerves of a 50-year-old male whose left, dominant hand had been amputated 21 years previously. Subsequent experiments involved 1) recording from USEAs for real-time control of a virtual prosthetic hand; 2) stimulation to evoke somatosensory percepts; and 3) closed-loop sensorimotor control. Overall, partial motor control and sensation were achieved using USEAs. 1) Isolated action potentials recorded from nerve motor fibers, although sparse at these distal implant sites, were activated during fictive movements of the phantom hand. Unlike in our previous two subjects, electromyographic (EMG) activity contributed to most online recordings and decodes, but was reduced in offline analyses using common average referencing. Online and offline Kalman-filter decodes of thresholded neural or EMG spikes independently controlled different digits of the virtual hand with one or two degrees of freedom. 2) Microstimulation through individual electrodes of the two USEAs evoked up to 106 different percepts, covering much of the phantom hand. The subject discriminated among five perceived stimulus locations, and between two somatosensory submodalities at a single location. 3) USEA-evoked percepts, mimicking contact with either a near or distal virtual target, were used to terminate movements of the virtual hand controlled with USEA recordings comprised wholly or mostly of EMG. These results further indicate that USEAs can help restore sensory and motor function after hand loss.